Carbon nanotubes accelerate acetoclastic methanogenesis: From pure cultures to anaerobic soils. (November 2020) - Xiao, Leilei; Zheng, Shiling; Lichtfouse, Eric; Luo, Min; Tan, Yang; Liu, Fanghua
Abstract: Direct interspecies electron transfer (DIET) between electricigens and methanogens has been shown to favour CO2 reduction to produce biomethane. Furthermore, DIET is accelerated by conductive materials. However, whether conductive materials can promote other methanogenic pathways is unclear due to a lack of detailed experimental data and the poor mechanistic studies. Here, we hypothesized that conductive carbon nanotubes (CNTs) stimulate acetoclastic methanogenesis independently of electricigens in pure cultures of Methanosarcina spp. and anaerobic wetland soil. We found a significant increase in the methane production rate during the growth phase, e.g. from 0.169 mM to 0.241 mM after addition of CNTs on the 3rd day. CNTs did not increase the abundance of electromicroorganisms or the electron transfer rate in anaerobic soils, using via microbial diversity and electrochemical analysis. 13 C–CH3 COOH labelling, stable carbon isotope fractionation and the CH3 F inhibitor of acetoclastic methanogenesis were used to distinguish methanogenic pathways. CNTs mainly accelerated acetoclastic methanogenesis rather than CO2 reduction in both pure cultures and anaerobic soils. Furthermore, the presence of CNTs slightly alleviate the inhibition of CH3 F on acetoclastic methanogenesis during the pure culture of Methanosarcina barkeri and Methanosarcina mazei with the production of more than 0.3 mM methane. CNTs closely attached to the cell surface were observed by transmission electron microscopy. Proteome analysis revealed a stimulation of protein synthesis with about twice the improvement involved in –COOH oxidation and electron transfer. Overall, our findings demonstrate that conducting CNTs favor methane production and that the mechanism involved is acetoclastic methanogenesis via acetate dismutation, at least partly, rather than classical CO2 reduction. Graphical abstract: Image 1 Highlights: Carbon nanotubes improved methane accumulation from acetoclastic methanogenesis. Proteome revealed the mechanism of increased CH4 production by promoting carboxyl oxidation. Direct acetate dismutation mainly contributed to CH4 production in wetland soil. A CNT-mediated model was suitable for both pure culture and diverse microbial communities.